1. 4x + 2 = -10
2. 7x + 12 = -9
Answer:
1. x = -3
2. x = -3
Step-by-step explanation:
1.
First subtract 2.
4x = -12
Divide by 4.
x = -3
2.
Subtract 12 from both sides.
7x = -21
Divide by 7
x = -3
Answer:
1. -3
2. -3
Step-by-step explanation:
Answer:
I dont know
Step-by-step explanation:
For this case we have that the main function is given by:
We apply the following transformation:
Vertical displacements:
Assume k> 0
To graph y = f (x) - k, move the graph k units down.
For k = 3 we have:
Answer:
when the function is changed to f (x) - 3 the change that will occur is:
Vertical displacement 3 units down.